The Impact of Cultural Globalization on Gender Norms - Latif, Muchtazar (Journal Social Humanity Perspective, 2024)
This study examines the impact of cultural globalization on gender norms using a quantitative research design. By analyzing data from a diverse sample of 1,200 respondents, the study investigates how exposure to global cultural products influences attitudes towards gender roles. The findings reveal that younger and more educated individuals tend to hold more progressive views on gender equality, highlighting the significance of educational initiatives and generational shifts. The results indicate a moderate to high level of engagement with international media, music, and social media, correlating with more egalitarian attitudes. However, the study also identifies the dual nature of cultural globalization, where global media can both promote progressive gender norms and reinforce traditional stereotypes. The research underscores the importance of a balanced approach in policy and education to foster positive aspects of globalization while respecting local cultural integrity and addressing potential negative impacts. The study contributes to a deeper understanding of the complex dynamics between global cultural flows and local gender norms, providing a foundation for future research and policy development aimed at promoting gender equality in a globalized world.